Costs and benefits of immigration and multicultural interaction - Moritz Bonn (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2012)
This paper studies how the existence of a minority culture influences the well-being of the native population and its attitude towards immigrants. In this context, I assume that multicultural interaction can be advantageous for immigrants and natives if intercultural obstacles and communication problems are abolished. It is found that certain shares of the immigrant as well as of the native population have incentives to acquire knowledge of the respective other culture since it enables them to interact with each other. I find that immigrants are more likely to acquire knowledge of the domestic culture than vice versa what I attribute to differences in the respective population size, assortative matching behavior and potentially asymmetric learning costs. The model further predicts that natives who have sufficiently low costs of learning the foreign culture are willing to vote for free migration whereas those who have higher learning costs will be in favor of immigration restrictions.
Keywords: F22; J15; Z1; 330; Immigration; Cultural Interaction; Political Economy; Einwanderung; Interkulturelle Beziehungen; Lernprozess; Multikulturelle Gesellschaft; Public Choice; Theorie